Genesis 2-3 : the hidden polemic against excesses in royal ideology - Docterman, Daryl L. (2016)
Using primarily Yairah Amit’s work on hidden polemics as a template, plus Ancient Near Eastern literature, this work argues for a hidden polemic in Genesis 2-3 against certain excesses in royal ideology and practice. The key themes of knowledge and life— as well as other terms and motifs that are related to knowledge and life— are examined in Genesis 2-3 in connection with those same themes in other parts of the Old Testament and in the Ancient Near East. It is demonstrated that knowledge and life are common themes of royal ideology in the rest of the Old Testament and in the Ancient Near East in general. This ideology is often treated in a way that is favorable to kings and their ideology. However, there are other views that are not so favorable. Such views often involve hidden polemics that seek to protect the authors as well as the readers and/or hearers of the polemics. These polemics also, by their hidden nature, tend to draw the reader/hearer into the stories.